Supervision of Cargo Transportation Over UPPKB Subulussalam City : Policy Implementation Study Based on the Regulation of the Minister of Transportation Concerning Supervision of Freight Transportation Loads and the Implementation of Weighing of Motor Vehicles on the Road - Mahmuddin; Badruzzaman; Bustamam Ali (INDONESIAN JOURNAL OF SOCIAL POLITIC AND POLICY STUDIES, 2025)
Drivers and goods transport companies, vehicles, and the class of roads traveled, that safety and work allowances, loading procedures, lack of appropriate equipment, such as forklifts, straps, or dunnage, materials used to secure cargo can be sought that are safe and efficient, weighing facilities related to procedures for loading goods, and excess Goods Transport documents, for each vehicle inspected, constraints and resources, and supervision of Goods Transport delivery related to assisting violations of Goods Transport, and the tendency for road damage caused by excess, Research objectives: 1). To find out and analyze the procedures for loading goods transport equipment at the Subulussalam City UPPKB. To find out and analyze the process of goods transport weighing facilities at the Subulussalam City UPPKB. Descriptive qualitative approach, data collection technique using (1). Observation (2). Interview (3). Documentation. The results show that drivers and freight transport companies face interrelated obstacles, but with different perspectives, long waiting times, the practice of illegal levies (Pungli), drivers often feel pressured to give money so that the weighing process runs smoothly, especially if they are carrying excess loads, loading procedures, a number of obstacles faced, both from the operational side in the field and broader managerial aspects. This problem occurred directly during the rearrangement of loads at UPPKB. Limited facilities and infrastructure: many UPPKBs do not have adequate facilities for the cargo transfer process. Small areas, lack of temporary storage warehouses for excess loads, weighing facilities, technical and infrastructure constraints, inadequate technology, old technology prone to damage and less accurate if not maintained properly, and supervision of goods transport loads, these constraints are not only technical, but also involve operational, human resource and even social aspects. Technical and infrastructure constraints, non-optimal weighing conditions